Digital competencies in public accounting professionals: The need for the new normal - Laverde Guzmán, Maria Yolanda (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of this research is to identify the needs of the leather, footwear and leather goods sector in the city of Bogota, in terms of digitalization. This is an exploratory, cross-sectional, mixed research, whose results show the urgent need for programs and strategies that allow small and micro-entrepreneurs to generate explicitly designed synergies that respond to solve neuralgic problems for these industries, in dynamics of knowledge transfer mainly at the level of technological competencies, support in digitization processes that help them to remain relevant in the new normality and to adapt to the dynamics that it imposes.